Uma proposta de ensino de geometria fundamentada na tendência metodológica história da matemática. 2020 - MORAIS, José Claudio Araujo (Universidade Federal do Tocantins, 2023)
We present in this work a study based on a bibliographic research, having as its starting point the following guiding question: how to insert the history of Mathematics in the teaching of Geometry? Thus, we elaborated a proposal to insert the History of Mathematics into the content of Geometry, taking into account some aspects of the geometry involved within the history of mathematics, seeking to encourage mathematics teachers to add new methods to teach this content in basic education. Therefore, we divided the work into two stages: the first consists of a theoretical survey that enabled us to better understand the historical concepts about the History of Mathematics and Geometry, as well as the study of official documents that deal with the teaching of geometry based on some authors. In the second stage, we present as a teacher proposal, where the History of Mathematics was inserted into the contents studied. Finally, as a result of this study, we realized that the use of the History of Mathematics as a methodological tool enables significant learning